Answer:
[tex]x = 1.48 \: and \: y = - 1.38[/tex]
Step-by-step explanation:
[tex]first \: equation[/tex]
[tex]x - 4y = 7[/tex]
[tex]second \: equation[/tex]
[tex]5x + y = 6[/tex]
[tex]from \: equation \: 1 \\ make \: x \: the \: subject \: of \: formula \\ x = 7 + 4y[/tex]
[tex]x =7 + 4y \: {equation \: 3}[/tex]
[tex]substitutefor \: x \: in \: equation \: 2[/tex]
[tex]5x + y = 6 \\ 5(7 + 4y) + y = 6 \\ 35 + 20y + y = 6 \\ 35 + 21y = 6 \\ 21 y = 6 - 35 \\ 21y = - 29 \\ [/tex]
[tex]y = \frac{ - 29}{21} [/tex]
[tex]y = - 1.38[/tex]
[tex]subsitute \: for \: y \: into \: equation \: 3[/tex]
[tex]x = 7 + 4y \\ x = 7 + 4( - 1.38) \\ x = 7 - 5.52 \\ x = 1.48[/tex]